Prevalence of Preterm Birth Recurrence and Related Factors in Ilam - Razhan Chehreh; Zoleikha Karamolahi; Azadeh Aevazi; Milad Borji; Azam Saffar (Mashhad University of Medical Sciences, 2018)
Introduction: Preterm birth and its risk of recurrence have long-term consequences on families and communities. So evaluating epidemiologic and environmental factors is important to diagnose the women at risk for early delivery. The present study aimed to investigate the prevalence of preterm birth recurrence and related factors. Methods: This cross-sectional study was conducted on a total of 3763 pregnant women referred to Shahid Mostafa Khomeini's maternity hospital in Ilam during July 2015 to July 2016. In this study, sampling was carried out in a sequential method. Data were collected using interviews and medical records of the pregnant women. The data gathering tool was a researcher-made questionnaire containing 37 questions, including demographic variables, midwifery history, and maternal medical and fetal variables (i.e., gestational age, number of previous births, birth weight, Apgar score, perinatal death, congenital malformation, previous preterm labor, placental abnormalities, , history of abortion, history of hypertension and diabetes during pregnancy, history of trauma and surgery, uterine and cervical disorder, premature rupture of the membranes). The data were analyzed using SPSS software (version 19), Chi-square test, and t-test. Results: Out of 350 neonates, 82.6% of them had no history of preterm labor, and 17.4% of the newborns had a history of preterm birth. The most prevalent recurrence of preterm delivery was at the age of 30-40 years. There was a statistically significant difference between the age, education level, parity, genital infection, urinary tract infection, history of surgery, diabetes, fetal death, fetal malformation, and preterm birth recurrence (P<0.05). Conclusion: Considering the high prevalence of preterm delivery in women with a history of preterm delivery, the prevention of this important complication of pregnancy can be performed by increasing clinical care and considering the causative factors.